Análise do comportamento de um solo argiloso marinho em ensaios de cisalhamento simples (DSS) cíclico - Fronza, Fernanda (2017)
Cyclic direct simple shear (DSS) tests in an offshore clay site have been performed and analyzed. Two types of tests have been carried out: stress controlled and strain controlled. The stress controlled tests were conducted in a commercial laboratory, where average shear stresses equal to zero and to fractions of the undrained shear strength obtained in monotonic conventional DSS tests. The strain controlled tests have been performed at COPPE/UFRJ, with average shear stresses equal to zero. The monotonic DSS tests performed in both laboratories have been compared. Monotonic DSS tests have also been conducted after cycling at COPPE/UFRJ. The behavior before and after cycling is also analyzed.